Ametropias y su influencia en el aprendizaje de alumnos con sindrome de down en la Unidad Educativa Nuestra Señora del Carmen Ricaurte, Los Ríos, octubre 2018 – abril 2019 - Orozco Arechua, Joselin Mariuxi (2019)
In addition to the anomalies frequently experienced by people with Down syndrome, trisomy 21 may have effects on the developing eye and may affect vision later. More than 60% of these patients present an eye problem due to the slow development of the eye and it is very important to pay attention to their vision from the first months of life. Vision plays such an important role in a person with Down syndrome since it is the fundamental basis of the learning process that they develop as children, this is because their condition is highly affected and their teaching methods are directed to capture their attention through images, figures, drawings, etc. All of the aforementioned impulse that the following investigation was carried out in the "Unidad Educativa Nuestra Señora Del Carmen" located in the Ricaurte parish, in the province of Los Ríos, with the purpose of knowing how ametropia influences student learning with Down syndrome. To carry out the whole project a hypothetical - deductive method was implemented that allowed to find the problems derived from a general problem, by means of a field investigation where there was a direct observation of the object of study, at the same time a series of surveys were applied, visual checks and tests to obtain results and conclusions. Regarding results and conclusions, it was found that there was a large percentage of students with untreated ametropias who were interfering with the progress of learning, so the parents, representative and teachers were explained about the advantages of taking care of visual health of children and how to prevent possible ametropia.